Measurement of water adsorption on aqsoa type zeolites under static and dynamic conditions - Fung, Xue Feng (2016)
There has been an increase in the research of adsorption chillers in recent years due to more emphases of nations in more environmentally friendly and energy saving technologies. The development of adsorption chiller has strong interest as compared to conventional mechanical compression chillers and heat pump as it uses waste heat and does not have environmentally unfriendly chlorofluorocarbons. Recently, there are new adsorbents called AQSOA-Z01 and AQSOA-Z02 zeolites and was developed by Mitsubishi Plastics Inc. The experiments were carried out to understand the behaviour of these two materials under static and dynamic conditions. In order to understand the characteristics and property of both zeolites, N2 adsorption or desorption isotherm using Brunauer-Emmett-Teller (BET) equation and scanning electron microscopy (SEM) are conducted. The amount and rate of uptakes of the adsorbate (water vapour) on the adsorbents (AQSOA-Z01 and AQSOA-Z02) were measured for the temperatures of 298K, 313K and 333K with the pressure ranging from 0.0222kPa to 17.971kPa or relative pressure ranging from 0.1 to 0.9. The adsorption uptakes data were then fitted with isotherm models such as Tóth, Dubinin Astakhov, Modified Langmuir and Chakraborty-Sun isotherm for studying static conditions. AQSOA-Z01 has a unique ‘S’ shaped adsorption isotherm of Type V and AQSOA-Z02 observed to have a Type I isotherm. The ‘S’ shaped represents a hydrophobic behaviour at low pressure. The Modified Langmuir isotherm was identified to fit the data for both AQSOA-Z01 and AQSOA-Z02. The difference between the adsorption and desorption isotherm is called the hysteresis behaviour. Qst was calculated using Clausius Clapeyron relations with experimental data, other Qst derived from these isotherms were also added for comparison. However, none of the derived Qst is able to fit the experimental data for both AQSOA-Z01 and AQSOA-Z02. To understand the behaviour of AQSOA-Z01 and AQSOA-Z02 under dynamic conditions, the kinetic model such as Modified Linear Driving Force model was used. Modified Langmuir was used to for the study of kinetic models and Modified Linear Driving Force model is considered to be a good model as it fits the experimental data for both AQSOA-Z01 and AQSOA-Z02. The data acquired from experiments were plotted against isotherm and kinetic model with margin of error of around 5% for a good fitting.